Induction of Antihuman C–C Chemokine Receptor Type 5 Antibodies by a Bovine Herpesvirus Type-4 Based Vector - Verna, Andrea Elizabeth; Franceschi, Valentina; Tebaldi, Giulia; Macchi, Francesca; Menozzi, Valentina; Pastori, Claudia; Lopalco, Lucia; Ottonello, Simone; Cavirani, Sandro; Donofrio, Gaetano (Frontiers in Immunology, 2017)
Bovine herpesvirus 4 (BoHV-4) is a promising vector for the delivery and intracellular expression of recombinant antigens and can thus be considered as a new prototype vaccine formulation system. An interesting, and actively pursued, antigen in the context of HIV infection prophylaxis (and therapy) is the CCR5 co-receptor, whose blockage by specific antibodies has been shown to inhibit both viral entry and cell-to-cell transmission of the virus. Building on our previous work on the BoHV-4 vector system, we have engineered and tested a replication-competent derivative of BoHV4 (BoHV-4-CMV-hCCR5ΔTK) bearing a human CCR5 expression cassette. We show here that CCR5 is indeed expressed at high levels in multiple types of BoHV-4-CMV-hCCR5ΔTK-infected cells. More importantly, two intravenous inoculations of CCR5-expressing BoHV-4 virions into rabbits led to the production of anti-CCR5 antibodies capable of reacting with the CCR5 receptor exposed on the surface of HEK293T cells through specific recognition of the amino-terminal region (aa. 14-34) of the protein. Given the growing interest for anti-CCR5 immunization as an HIV control strategy and the many advantages of virus-based immunogen formulations (especially for poorly immunogenic or self-antigens), the results reported in this study provide preliminary validation of BoHV-4 as a safe viral vector suitable for CCR5 vaccination.